Эффективность экологического контроля загрязнения земель производственных площадок - Уберман, В. И.; Васьковец, Людмила Антоновна (НТУ "ХПИ", 2006)
Розроблена система якісних критеріїв для оцінки екфективності дій при екологічному контролі забруднення земель виробничих майданчиків підприємств. Ці критерії перевірені на прикладі державного контролю виробничого майданчика підприємства ВАТ "Тепловозоремонтний завод", м. Полтава, для випадка пріоритетної забруднюючої речовини - свинця. Критерії охоплюють усі ланки процедури контролю, від визначення еколого-правового статусу об'єкта до можливої шкоди від забруднення. Критерії призначені для використання в еколого-інспекторській діяльності, при проведенні науково-технічних, екологічних, судових експертиз та арбітражних дослідженнях.

The system of quality criteria for assessing the efficiency of environmental inspection of polluted soils within sites of industrial enterprises (plants) is developed. These criteria were verified for the example of state inspection on industrial site of JSC "Heat-engine locomotive repairing plant" in Poltava city, for the case of lead contaminant one from heavy metal priority pollutants. These criteria describe and include all stages of inspection procedure, from determination of environmental law status for inspected site to possible harm (damage) caused given pollution. Proposed criteria intend as for use in environmental inspection activity, as for different kinds of expertise: scientific and engineering, environmental, legislation expertise, and for arbitrage examinations.
Keywords: площадки промышленных предприятий; ППП; земли производственных площадок; ЗПП; источник загрязнения атмосферы; ИЗА; выбросы; экологический контроль